Dampak Sosiologis Keberadaan Wisata Kuliner Dalam Peningkatan Kesejahteraan Keluarga Di Kecamatan Aur Birugo Tigo Baleh - Handrina, Emi; Gusnayetti, Gusnayetti; B, Doddie Arya Kusuma (CV. ITTC INDONESIA, 2024)
The emergence of culinary tourism in the Aur Kuning subdistrict, Aur Birugo Tigo Baleh subdistrict was founded by business people and assisted and developed by the surrounding community. Culinary tourism requires supporting resources to be able to create a positive effect on the community's economy. This means that people also need seriousness in helping to create a good image for the tourist attraction, so that it will invite tourists to visit there. the friendliness and honesty of the people can create a special impression, so that it can arouse interest in coming back. The role of the community is very much needed to create favorable conditions for tourism development. Community participation around tourist attractions can be realized in trade objects or services such as souvenir shops that sell various souvenirs, photography and so on. Good cooperation is really needed between the managers of culinary tourism objects and the community around the tourist attraction. The community will provide support if it is considered that the business can have a positive effect on them, especially in improving the standard of living or the economy of the community, therefore this research is important to carry out to see the impact of the existence of culinary tourism in the Aur Kuning sub-district, Aur Birugo Tigo Baleh District